A case study of abandoned housing projects in Selangor - Muhammad Faizal, Abdul Rahman (2018)
Housing industry is one of the most dynamic, risky, and challenging industries. In Selangor, this industry has a poor reputation for managing risks, with many major projects failing to be completed within the allotted time. Due to the inherent risks involved in construction projects, it is essential to recognize the risks that cause problems associated with abandoned housing projects. Therefore, this study aims to identify the risks that contribute to issues of abandoned housing projects and to propose suitable solution to overcome this. The questionnaire had been distributed to the respondent with the background of civil engineering. The average index method was used to analyse the data. The results show that many risks are involved in housing project, including risks related to environmental impacts, construction, politics, law, management and finance. The respondent agreed that the abandoned housing project is causes by this main factors. It was also found that all relevant parties involved in housing industry are required to have extensive cooperation in advance and should perform systematic risk management strategies in order to mitigate the risks leading to problems associated with abandoned housing projects.